2020
DOI: 10.1038/s41467-020-14605-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional effects of copy number alterations in a large set of human cancers

Abstract: Copy number alterations (CNAs) can promote tumor progression by altering gene expression levels. Due to transcriptional adaptive mechanisms, however, CNAs do not always translate proportionally into altered expression levels. By reanalyzing >34,000 gene expression profiles, we reveal the degree of transcriptional adaptation to CNAs in a genome-wide fashion, which strongly associate with distinct biological processes. We then develop a platformindependent method-transcriptional adaptation to CNA profiling (TACN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 39 publications
1
78
0
Order By: Relevance
“…Altogether, it is essential to consider that changes in CNAs could not affect gene expression levels due to transcriptional adaptative mechanisms. A recent study used a new method, known as transcriptional adaptation to CNA profiling (TACNA), and found a strong correlation of expression levels changes by CNAs with mean methylation from TCGA datasets [ 47 ]. These findings suggest that dysregulation of the epigenome could be one of the underlying mechanisms driving the translational response to CNAs, and further studies could help to understand the impact of the results regarding tumor suppressors involved in the chromatin modification mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, it is essential to consider that changes in CNAs could not affect gene expression levels due to transcriptional adaptative mechanisms. A recent study used a new method, known as transcriptional adaptation to CNA profiling (TACNA), and found a strong correlation of expression levels changes by CNAs with mean methylation from TCGA datasets [ 47 ]. These findings suggest that dysregulation of the epigenome could be one of the underlying mechanisms driving the translational response to CNAs, and further studies could help to understand the impact of the results regarding tumor suppressors involved in the chromatin modification mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Castagnola et al found that only OPMDs on the tongue mucosa showed a major frequency of aneuploidy confronted to OPMDs on buccal mucosa [73], which highlights the possibility that only OPMDs limited to tongue mucosa may benefit from immunotherapy treatment. Moreover, Bhattacharya et al found four genes associated with decreased CD8+ T-cell number in the microenvironment of tumor when transcriptionally affected by copy number alterations [74]. It is known that a large number of CD8+ T cells is associated with major response rates to immune checkpoint inhibitors [75,76].…”
Section: Mutational Load and Immunology: Should These Factors Be Analmentioning
confidence: 99%
“…Firstly, we used c-ICA to segregate the average expression patterns of complex biopsies into statistically independent components (Bhattacharya et al, 2020;Biton et al, 2014;Kong et al, 2008). Metabolic processes relevant to cancer biology can be challenging to detect when their transcriptional footprints (TFs) are subtle and concealed by more pronounced TFs from other biological processes and experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we collected gene expression data from four databases: the Gene Expression Omnibus (GEO dataset, n = 21,592), The Cancer Genome Atlas (TCGA dataset, n = 10,817), the Cancer Cell Line Encyclopedia (CCLE dataset, n = 1,067), and the Genomics of Drug Sensitivity in Cancer (GDSC dataset, n = 1,018) ( Figure 1A), totaling 34,494 samples (Bhattacharya et al, 2020). Of this total, 28,200 expression profiles originated from patient-derived complex tissue cancer biopsies, 4,209 from complex tissue biopsies of non-cancerous tissue, and 2,085 from cell lines.…”
Section: A Subset Of Transcriptional Components Is Associated With Mementioning
confidence: 99%
See 1 more Smart Citation